Estimating the sensitivity of the expanded OVRO-LWA array to cosmic-ray primary composition - Carvalho, W. R.; Romero-Wolf, A.; Belov, K.; D'Addario, L.; Anderson, M.; Eastwood, M.; Hallinan, G.; Kocz, J.; Lamb, J.; Monroe, R.; Nelles, Anna; Plant, K. (Proceedings of Science, 2021)
In this study we investigate the capability of the planned expansion of the Owens Valley Long Wavelength Array (OVRO-LWA) to perform radio based composition studies of the cosmic-ray flux between 50 PeV and 1 EeV. We use ZHAIRES simulations in conjunction with a method similar to the one developed by the LOFAR experiment, but that only uses radio data between 30 and 80 MHz, to reconstruct the depth of shower maximum Xmax. We found that the lower antenna densities away from the central core of the array lead to a decrease in the effective area for quality Xmax reconstructions of low zenith angle events, and that the asymmetry of the array layout creates the need for quality cuts that depend on arrival direction. We also investigate the dependence of Xmax uncertainties on shower energy and arrival direction and show that at 500 PeV it is possible to obtain Xmax uncertainties lower than 20 g/cm2 for the majority of arrival directions by using a set of simple cuts. For energies below 1017 eV, alternative reconstruction methods, such as the use of hierarchical beamforming to increase SNR or the use of arrival time measurements on the ground may be needed to maintain Xmax resolution at a desirable level.
CRIS-Team Scopus Importer:2023-08-15